Efeitos do treinamento resistido sobre a expressão gênica de moléculas envolvidas na oxidação de gordura e na lipogênese no fígado de ratas ovariectomizadas - Domingos, Mateus Moraes (2011)
Decreased levels of estrogen are associated with hepatic steatosis (HS), through changes in gene expression of molecules related to fat oxidation and lipogenesis. Both resistance training (RT) and endurance training (ET) prevents the HS in ovariectomized (Ovx) rats. However, the molecular events associated with this process were only investigated for ET but not for RT. Aims: Thus, the aim of this study was to investigate the effects of Ovx and RT on the gene expression of molecules related to fat oxidation and lipogenesis in the liver of rats. Methods: Sprague-Dawley adult female rats were grouped into four groups (n = 6 per group): sham-operated sedentary (Sham-Sed); Ovx sedentary (Ovx-Sed); sham-Rt and Ovx- Rt. A 10-week RT period, during which the animals climbed a 1.1-m vertical ladder with weights attached to their tails, was used. The sessions were performed three times a week, with 4-9 climbs and 8-12 dynamic movements per climb. Gene expression was analyzed by RT-PCR by the ΔΔCt method. Results: The estrogen deficiency associated with ovariectomy decreased the gene expression of molecules related to fat oxidation, carnitine palmitoyltransferase I (53%) and β-hydroxyacyl-CoA dehydrogenase (27%), and increased of molecules related to lipogenesis, sterol regulatory element-binding protein-1c (106%), acetyl-CoA carboxilase (ACC) (72%) and stearoyl CoA desaturase-1 (109%), which had their expression restored to the RT, with the exception of the ACC. Conclusions: The present results indicate that the RT may have important effects on the prevention of HS in Ovx animals, possibly through the restoration in gene expression of molecules related to hepatic lipid metabolism